Autophagy in health and disease. 5. Mitophagy as a way of life - Gottlieb, Roberta A. (American Physiological Society, 2010)
Our understanding of autophagy has expanded greatly in recent years, largely due to the identification of the many genes involved in the process and to the development of better methods to monitor the process, such as green fluorescent protein-LC3 to visualize autophagosomes in vivo. A number of groups have demonstrated a tight connection between autophagy and mitochondrial turnover. Mitochondrial quality control is the process whereby mitochondria undergo successive rounds of fusion and fission with a dynamic exchange of components to segregate functional and damaged elements. Removal of the mitochondrion that contains damaged components is accomplished via autophagy (mitophagy). Mitophagy also serves to eliminate the subset of mitochondria producing the most reactive oxygen species, and episodic removal of mitochondria will reduce the oxidative burden, thus linking the mitochondrial free radical theory of aging with longevity achieved through caloric restriction. Mitophagy must be balanced by biogenesis to meet tissue energy needs, but the system is tunable and highly dynamic. This process is of greatest importance in long-lived cells such as cardiomyocytes, neurons, and memory T cells. Autophagy is known to decrease with age, and the failure to maintain mitochondrial quality control through mitophagy may explain why the heart, brain, and components of the immune system are most vulnerable to dysfunction as organisms age.